Single-cell atlas of human pancreatic islet and acinar endothelial cells in health and diabetes - Rebecca Craig-Schapiro; Ge Li; Kevin Chen; Jesus M. Gomez-Salinero; Ryan Nachman; Aleksandra Kopacz; Ryan Schreiner; Xiaojuan Chen; Qiao Zhou; Shahin Rafii; David Redmond (Nature Communications)
Abstract Characterization of the vascular heterogeneity within the pancreas has previously been lacking. Here, we develop strategies to enrich islet-specific endothelial cells (ISECs) and acinar-specific endothelial cells (ASECs) from three human pancreases and corroborate these findings with three published pancreatic datasets. Single-cell RNA sequencing reveals the unique molecular signatures of ISECs, including structural genes COL13A1, ESM1, PLVAP, UNC5B, and LAMA4, angiocrine genes KDR, THBS1, BMPs and CXCR4, and metabolic genes ACE, PASK and F2RL3. ASECs display distinct signatures including GPIHBP1, CCL14, CD74, AQP1, KLF4, and KLF2, which may manage the inflammatory and metabolic needs of the exocrine pancreas. Ligand-receptor analysis suggests ISECs and ASECs interact with LUM+ fibroblasts and RGS5+ pericytes and smooth muscle cells via VEGF-A:VEGFR2, CXCL12:CXCR4, and LIF:LIFR pathways. Comparative expression and immunohistochemistry indicate disruption of endothelial-expressed CD74, ESM1, PLVAP, THBD, VWA1, and VEGF-A cross-talk among vascular and other cell types in diabetes. Thus, our data provide a single-cell vascular atlas of human pancreas, enabling deeper understanding of pancreatic pathophysiology in health and disease.